The Effectiveness of Interactive Demonstration in Improving Tooth Brushing Techniques School-Aged Children - Astarani, Kili; Kurniawan, Fidiana; Cahyani, Dinar Yuni Awalia Anilam (Journal of Ners and Midwifery, 2026)
Incorrect tooth brushing techniques in school-aged children can lead to dental and oral problems, such as tooth decay, cavities, and dental caries. One approach used to improve good tooth brushing habits is through demonstrations. Interactive demonstrations are an effective method to enhance school children's understanding, helping them develop the correct knowledge and habits for proper tooth brushing. This study aims to analyze the effectiveness of interactive demonstrations in improving proper tooth-brushing techniques among school-aged children at SD YBPK Kediri. The research design was a pre-experiment with a one-group pre-test and post-test design. The population consisted of 32 fourth and fifth-grade students at SD YBPK Kediri. The inclusion criteria for the study were children aged 7–12 years, those who attended school during data collection, and those willing to participate in the study. A total sampling technique was applied. Data were analyzed using the Wilcoxon test. Before the interactive demonstration, the children's tooth brushing behavior was suboptimal, with 22 respondents (68.8%) demonstrating inadequate brushing techniques. There was a significant improvement in tooth brushing techniques after the interactive demonstration, with a significance value of 0.000 (p < 0.05). The interactive demonstration was found to be highly effective in improving tooth-brushing behavior among school-aged children at SD YBPK Kediri